DEACTIVATION OF BIOCIDES IN INDUSTRIAL WATER TREATMENT - Williams Terry М.; McGinley, Heather R.; Wood, Paul L. (WATER AND WATER PURIFICATION TECHNOLOGIES. SCIENTIFIC AND TECHNICAL NEWS, 2012)
Industrial biocides are used for microbial control in a variety of industrial water systems including, cooling, paper, oilfield, and membrane applications. Biocide treatment programs are typically designed to provide optimal results based on environmental conditions, regulatory needs, efficacy, and cost. An important area of concern relating to biocide use is discharge of the treated effluent (ex., blowdown) into waste treatment systems or natural waters. Regulatory requirements also impact the amount of biocide that may be released. In many cases, the biocide must be effectively deactivated or neutralized prior to discharge of the effluent. This paper will provide a review of the specific methods for deactivating the various oxidizing and non-oxidizing biocides commonly used today. Examples of lab and field data will be presented.